(untitled) (Research, Society and Development, 2021)
The aim of this study was to characterize the population with ostomy treated at the Specialized Rehabilitation Center and to verify the user’s perception of quality, safety, quantity and frequency of exchange of equipment provided by the service. This is a cross-sectional study carried out in an Ostomy Care Service in the interior of the state of São Paulo, Brazil. 126 people with intestinal ostomy were interviewed between the months of April and June 2019, on the day scheduled for the acquisition of the equipment. Among the study participants, 62.90% were male and 64.29% with permanent ostomies; 80.16% said they were totally satisfied with the quality of the material received and 67.46% expressed total security with the use of the collecting equipment; 92.08% said they were satisfied with the guidance received by the health team and materials received. Statistical tests did not show dependence between the quality of the collecting equipment and the other variables (p > 0.05). Most respondents reported being satisfied with the quality of the equipment and the care provided by the service. The importance of the stomatherapist nurse is highlighted, as it is essential in the care of patients with ostomies, from the preoperative period and postoperative follow-up, with indication of the appropriate collecting equipment to achieve the rehabilitation and development of the autonomy of the person who has an ostomy.